2018
DOI: 10.1152/ajpcell.00230.2018
|View full text |Cite
|
Sign up to set email alerts
|

Copper transporter ATP7A interacts with IQGAP1, a Rac1 binding scaffolding protein: role in PDGF-induced VSMC migration and vascular remodeling

Abstract: Vascular smooth muscle cell (VSMC) migration contributes to neointimal formation after vascular injury. We previously demonstrated that copper (Cu) transporter ATP7A is involved in platelet-derived growth factor (PDGF)-induced VSMC migration in a Cu- and Rac1-dependent manner. The underlying mechanism is still unknown. Here we show that ATP7A interacts with IQGAP1, a Rac1 and receptor tyrosine kinase binding scaffolding proteins, which mediates PDGF-induced VSMC migration and vascular remodeling. In cultured r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…ATP7A Silencing Reduces Single Breast Cancer Cell Migration Velocity and Directionality. Since recent studies showed ATP7A to be important for metastasis in a different breast cancer system (20) and for stimulated migration of vascular smooth-muscle cells (38), we decided to test if ATP7A is also involved here, with Atox1, to promote MDA-231 breast cancer cell migration. To test involvement of ATP7A, we assessed cell migration in control versus ATP7A-silenced cells with the same methodology as for Atox1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP7A Silencing Reduces Single Breast Cancer Cell Migration Velocity and Directionality. Since recent studies showed ATP7A to be important for metastasis in a different breast cancer system (20) and for stimulated migration of vascular smooth-muscle cells (38), we decided to test if ATP7A is also involved here, with Atox1, to promote MDA-231 breast cancer cell migration. To test involvement of ATP7A, we assessed cell migration in control versus ATP7A-silenced cells with the same methodology as for Atox1.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work showed Atox1 to be important for PDGF-stimulated smooth-muscle cell migration, and it was suggested that in these cells Atox1 mediates migration via interactions with ATP7A and Rac1 (34). This work was followed by another study, using the same smooth-muscle cells, where it was shown that cell migration is promoted by ATP7A interactions with IQGAP1 (IQ motif containing GTPase activating protein 1) and Rac1, whereby all proteins translocate to the leading edge of the cells (38). IQGAP1 is a Rac1-binding scaffolding protein that plays a central role in the assembly of signaling complexes that regulate cellular motility, morphogenesis, and cell adhesion (43).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the ATP7A protein, it is also deregulated in many cancers, such as in pancreatic cancer, where ATP7A is upregulated compared to that in chronic pancreatitis [60]. The ATP7A protein plays an important role in the formation of metastases in breast cancer and induces the migration of vascular smooth muscle cells [130]. In addition, high levels of ATP7A expression in primary tumors are associated with reduced survival according to publicly available databases [131].…”
Section: Involvement Of Copper Metabolism Proteins In Metastasis Formationmentioning
confidence: 99%
“…ATP7A protein is also deregulated in many cancers, such as in pancreatic cancer where ATP7A is upregulated compared to chronic pancreatitis [52]. The ATP7A protein plays an important role in the formation of metastases in breast cancer and induces the migration of vascular smooth muscle cells [53]. In addition, high levels of ATP7A expression in primary tumors are associated with reduced survival according to publicly available databases [54].…”
Section: The Use Of Copper Proteins As Cancer Biomarkersmentioning
confidence: 99%